From Programming to Products: Softalk Magazine and the Rise of the Personal Computer User. - Nooney, Laine; Driscoll, Kevin; Allen, Kera (Information & Culture, 2020)
In the 1980s, the user emerged as a distinct class of personal computer owner motivated by instrumental goals rather than the exploratory pleasures of hackers and hobbyists. To understand the changing values and concerns of microcomputer owners, we analyzed 1,285 reader letters published in Softalk magazine between 1980 and 1984. During this period, a preoccupation with programming was displaced by discussions of software applications, products, and services. This transition illustrates the separation of users from hobbyists, reflecting changes in the software industry and attitudes toward amateurism, professionalization, gender, and expertise.